SINTESIS ANALOG KURKUMIN TURUNAN 1-BENZIL 4-PIPERIDINON MENGGUNAKAN KATALIS BASA DAN UJI AKTIVITAS SEBAGAI ANTIBAKTERI - Wahyuni, S.; Eryanti, Y.; Zamri, A. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Curcumin is one of secondary metabolites with phenolic group which was known tohave various biological activities such as antimicroba, anticancer, antioxidant, antitumorand anti-inflammatory activities. In this research, curcumin analog of 1-benzil-4-piperidone derivative was synthesized using microwave irradiation with catalyst NaOH.The rendement (YN 2 ) resulted 99.39%. All compounds were characterized using UVspectrophotometer, IR spectrophotometer, 1 H NMR, and 13 C NMR spectrometers. Theantibacterial activity was evaluated using the agar diffusion method. Antibacterialactivity test was carried out at concentrations of 20, 30, 40, 50 , and 60 mg/disc againstGram positive bacteria (Staphylococcus aureus and Bacillus subtilis) and Gramnegative bacteria (Escherichia coli and Salmonella enteritidis). YN 2 compoundsobtained showed different antibacterial activity against different bacteria.